2017
DOI: 10.18178/jocet.2017.5.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis for Small Scale Production of Rubber Seed Oil and Biodiesel in Palangkaraya, Indonesia

Abstract: Abstract-Estimation of production cost and sensitivity analysis for small scale production of rubber seed oil and biodiesel was studied. The production unit is projected to be built in the ex-Mega Rice Project area south of Palangkaraya, Indonesia which has a serious land degradation and deforestation problem. The valorization of rubber seed to produce bioproducts is seen as a contribution to revitalize the area. The production cost for rubber seed oil and rubber seed biodiesel in a small-scale (55 ton/y) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Abduh et al reported that the production cost of producing rubber seed oil operating at a capacity of 55 ton/y at this location was approximately €0.42/L. Abduh et al concluded on the basis of this study that RSO may be a competitive renewable resource for stationary electricity generation using a diesel engine [31].…”
Section: Comparison Of the Acid Value Versus Time Profiles For Rubbermentioning
confidence: 67%
“…Abduh et al reported that the production cost of producing rubber seed oil operating at a capacity of 55 ton/y at this location was approximately €0.42/L. Abduh et al concluded on the basis of this study that RSO may be a competitive renewable resource for stationary electricity generation using a diesel engine [31].…”
Section: Comparison Of the Acid Value Versus Time Profiles For Rubbermentioning
confidence: 67%
“…For the second aspect, minimizing waste may refer to the valorization of the outer shell of the rubber seeds that are typically removed prior to the isolation of oil from the dehulled rubber seeds. Abduh et al (2017b) has demonstrated that the shell may be used as one of the substrates for the cultivation of Hermetia illucens to produce protein and oil rich biomass. For the third aspect, maximizing profit may be attained by producing co-products apart from biodiesel and glycerol.…”
Section: Small Scale Production Of Biodieselmentioning
confidence: 99%
“…For the third aspect, maximizing profit may be attained by producing co-products apart from biodiesel and glycerol. The pressed cake obtained after the isolation of oil may be further valorized as cattle feed it still contains a relatively high amount of protein (Widyarani, 2014;Abduh et al, 2017b).…”
Section: Small Scale Production Of Biodieselmentioning
confidence: 99%
“…A small amount of good quality seeds can be used for propagation. The oil, being one of the components that is present in the highest amount, is an interesting product that is currently getting more attention mainly as an alternative feedstock for biodiesel production [6,18]. Valorisation of oil alone, however, may not be economically feasible [18].…”
Section: Seedmentioning
confidence: 99%
“…Less attention is given on proteins in the seeds and the leaves of rubber tree [16,17]. Rubber seed has been identified as a potential protein source, particularly after oil separation for biodiesel production [18,19].…”
Section: Introductionmentioning
confidence: 99%